P812 Fluorescently labelled vedolizumab identified macroscopic and microscopic mucosal drug distribution in patients with inflammatory bowel disease. (30th January 2023) - Van Der Waaij, A; Gabriëls, R; Linssen, M; Volkmer, P; Robinson, D; Hermoso, M; Karrenbeld, A; Festen, E; Dijkstra, G; Kats-Urgulu, G; Nagengast, W
Abstract: Background: Biological treatment in inflammatory bowel disease (IBD) patients is currently hampered by high non-response rates. To enhance personalized medicine and predict response to biological therapeutics such as vedolizumab, the working mechanism should be elucidated. We aimed to visualize macroscopic and microscopic vedolizumab distribution and detect drug target cells during quantified fluorescence molecular endoscopy (QFME) to improve understanding of the mechanism of action. Methods: Vedolizumab-800CW was developed and GMP produced. Forty-three QFME procedures were performed in thirty-seven IBD patients two to four days after intravenous administration of vedolizumab-800CW. Each QFME procedure consisted out of endoscopic assessment of the inflammation status per colonic segment by high-definition white light endoscopy, followed by real-time in vivo assessment of the macro-distribution of fluorescent vedolizumab-800CW signal and quantification by spectroscopy of selected segments. Dose escalation was performed using 0.0 mg, 4.5 mg and 15 mg. Subsequently, two patient cohorts were added that received a dose of 75 mg or 300 mg unlabelled vedolizumab prior to vedolizumab-800CW to assess target saturation. Tissue biopsies were obtained for histopathological assessment, for further ex vivo analysis of the fluorescent signal and for visualization of the microscopic distribution and identification of vedolizumab-800CW target cells by fluorescence microscopy (fig 1). Results: Both during in vivo QFME and ex vivo analysis a clear dose- and inflammation severity-dependent increase of the fluorescent drug signal was revealed (fig 2). A significant difference was found between the dose groups for non-inflamed (p=0.0004), mild inflamed (p=0.0397) and severe inflamed (p=0.0056) tissue. In addition, the difference in intrinsic fluorescence between the severe inflamed tissue and non-inflamed tissue was significant within the 15 mg (p<0.0001), 75 mg + 15 mg (p=0.0118) and the therapy + 15 mg group (p=0.0005). Fluorescence microscopy revealed clear membrane binding of vedolizumab-800CW to inflammatory cells and migration into the inflamed mucosa. Additional analyses to identify specific target cells are ongoing and immune compositions of regions with high and low vedolizumab signal will be unravelled. Conclusion: QFME using vedolizumab-800CW elucidated novel detailed macroscopic and microscopic vedolizumab distribution in the inflamed target organ. In addition, its shows the potential of QFME to better understand local drug distribution, target cell identification and target engagement, which could improve understanding of targeted drugs over standard pharmacokinetic and pharmacodynamic analysis.